Design and Simulation “Ha”-Slot Patch Array Microstrip Antenna for WLAN 2.4 GHz: Ivar Zekker3 - Sotyohadi, Sotyohadi; Somawirata, I Komang; Widodo, Kartiko Ardi; Phung, Son Thanh; Zekker, Ivar (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
This paper presents a linear 1 × 2 “Ha ( )”–slot patch array microstrip antenna. The proposed design of an array microstrip antenna is intended for Wireless Local Area Network (WLAN) 2.4 GHz devices. From the previous research concerning the single patch “Ha ( )”–slot microstrip antenna, the gain that can be achieved is 5.77 dBi in simulation. This value is considered too small for an antenna to accommodate WLAN devices if compare to a Hertzian antenna. To enhance the gain of microstrip antenna, some methods can be considered using linear 1 × 2 patch array and T-Junction power divider circuit to have matching antenna impedance. The distances between two patches are one of the important steps to be considered in designing the patch array microstrip antenna. Thus, the minimum distance between the patch elements are calculated should be greater than λ/2 of the resonance frequency antenna. If the distance less than λ/2 electromagnetically coupled will occur, vice versa when it is to widen the dimension of the antenna will less efficient. Epoxy substrate Flame Resistant 4 (FR4) with dielectric constant 4.3 is used as the platform designed for the array antenna and it is analyzed using simulation software Computational Simulation Technology (CST) studio suite by which return loss, Voltage Standing Wave Ratio (VSWR), and gain are calculated. The simulation result showed that the designed antenna achieve return loss (S11) -25.363 dB with VSWR 1.1 at the frequency 2.4 GHz, and the gain obtained from simulation is 8.96 dBi, which is greater than 64.4 % if compared to the previous one. The proposed antenna design shows that increasing the number of patches in the array can technically improve the gain of a microstrip antenna, which can cover a wider area if applied to WLAN devices